Etika Kristen Dalam Memandang Pernikahan Dini Pada Masyarakat Madura - Lay, Rut Novita; Efraim Tampubolon; Peter Neno; Indraldo Undras; Stephanie Erastus (Discreet: Journal Didache of Christian Education, 2023)
This research discusses the culture of early marriage in Madurese society with a focus on Christian ethics. Although this tradition still exists, there is a conflict between custom and national law regarding the age of marriage. Particularly in Jambu Monkey village, early marriage has serious repercussions, including girls dropping out of school and parental involvement in marriage decision-making. From the perspective of Christian ethics, marriage decisions should be based on piety and obedience to God, and early marriage is considered incompatible with these principles. The impacts of early marriage, including the potential for violence, economic hardship, and rapid population growth, are also discussed. The purpose of this study is to provide moral and ethical guidelines for Christians in addressing the issue of early marriage and to measure the social and moral consequences of early marriage in the context of Christian ethics.